Problems of psychological remote support of cancer patients in a COVID-19 pandemic - Stanovskyi Богдан (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of a distance report to the III scientific-practical conference with international participation "Psychosomatic medicine: science and practice". The following is a problem of psychological remote support of cancer patients in a pandemic COVID-19.